2020
DOI: 10.2147/ott.s283542
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exosomal Transfer of Macrophage-Derived miR-223 Confers Doxorubicin Resistance in Gastric Cancer</p>

Abstract: Purpose: Macrophages are a major component of the tumour microenvironment and play an important role in chemoresistance of cancer. However, how exosomal microRNAs (miRNAs) derived from macrophages contribute to the development of doxorubicin resistance in gastric cancer (GC) are not clearly defined. The aim of this study was to investigate whether macrophage-derived exosomes mediate doxorubicin resistance in GC. Methods: Exosomes isolated from macrophage culture medium were characterized and cocultured with GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“… [ 107 ] miR-223 miRNA Promote doxorubicin resistance in GC cells by inhibiting FBXW7. [ 108 ] Vincristine CLIC1 protein Induce the development of resistance to vincristine in vitro, which might relate to up-regulated P-gp and Bcl-2. [ 109 ] Paclitaxel miR-155-5p miRNA Induce EMT and chemo-resistant phenotypes from paclitaxel-resistant GC cells to the sensitive cells, which may be mediated by GATA3 and TP53INP1 suppression.…”
Section: The Relationship Between Sevs and Gcmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 107 ] miR-223 miRNA Promote doxorubicin resistance in GC cells by inhibiting FBXW7. [ 108 ] Vincristine CLIC1 protein Induce the development of resistance to vincristine in vitro, which might relate to up-regulated P-gp and Bcl-2. [ 109 ] Paclitaxel miR-155-5p miRNA Induce EMT and chemo-resistant phenotypes from paclitaxel-resistant GC cells to the sensitive cells, which may be mediated by GATA3 and TP53INP1 suppression.…”
Section: The Relationship Between Sevs and Gcmentioning
confidence: 99%
“…Additionally, sEVs may be involved in resistance to doxorubicin [ 107 , 108 ], vincristine [ 109 ] and paclitaxel [ 110 ]. However, some data seem to be from cell research and it is speculated that they may be found in sEVs as they belong to a group of molecules which are frequently found in sEVs.…”
Section: The Relationship Between Sevs and Gcmentioning
confidence: 99%
“…Zheng et al found that M2-polarized macrophage-derived exosome microRNA-21 can transfer to GC cells to inhibit cell apoptosis by downregulating PTEN and enhancing the activation of the PI3K/AKT signaling pathway, thereby inducing DDP resistance in GC patients (140). In addition, Gao and colleagues reported that macrophage-derived exosomes transferred miR-223 into cocultured GC cells to activate their resistance to ADR by targeting FBXW7, a p53-dependent tumor-suppressor protein (86).…”
Section: Exosomal Ncrna and Gc Chemotherapy Resistancementioning
confidence: 99%
“…Exosomes produced by other cells in the TME, such as CAF and M2 macrophages, can also induce chemoresistance in GC cells ( 85 , 86 , 140 ). Ferroptosis is a novel mode of non-apoptotic cell death induced by the accumulation of toxic lipid peroxides (lipid-ROS) in an iron-dependent manner ( 141 ).…”
Section: Biological Functions Of Exosomal Ncrnas In Gcmentioning
confidence: 99%
“…In addition, the macrophages of the tumor environment showing oncogenic effects are considered as tumor-associated macrophages (TAMs), which usually exhibit M2 phenotype ( Dessouki et al, 2020 ). The correlation between tumor cells and TAMs has been revealed some cancers (gastric cancer, pancreatic cancer, et al) ( Gao et al, 2020 ; Zhou et al, 2021 ). Nevertheless, the detailed association between NSCLC treatments with TAMs is unclear.…”
Section: Introductionmentioning
confidence: 99%